Análise do estado de conservação do manguezal do rio Sergipe - Soares, Marcelo Steinmetz (2016)
Mangroves are ecological systems at the interface between marine and terrestrial regions and subjected to natural disturbances of the stressful environment and anthropogenic actions due to urban development. The mangrove of the Rio Sergipe suffers high environmental pressure because this river, in addition to bathe the capital of the State of Sergipe and other cities in the region, is surrounded by agricultural areas and aquaculture tanks. The objective of this work was to analyze the state of conservation of this mangrove considering the structure of the vegetation, human interference by the presence and quantification of trash and burrows of crabs, regeneration capacity through the quantification of individuals regenerating and elaboration of environmental vulnerability map. The results obtained show that the mangrove vegetation of Rio Sergipe presents, for the most part, good condition considering their structure and composition. Aspects such as the presence and number of burrows of crabs give indications of anthropogenic interference. Environmental vulnerability analysis demonstrated a high degree of susceptibility considering the set of information about the type, use and occupation of the soil, geology, geomorphology and climate. Considering the set of information in this paper can be considered that the mangrove forest of Rio Sergipe is in good condition, but is susceptible to anthropogenic interference of various natures because of their degree of vulnerability and the occupation and human exploration. So it is recommended if intense surveillance and awareness of the importance of the mangrove forest.